Heritage and Global Language Use among Lithuanian-English Bilinguals: Language Maintenance and Identity Preservation in Kaunas - Annisa Budi Damayanti; Slamet Setiawan; Daiva Bartušienė (English Department, Universitas Negeri Surabaya, 2026)
The growing use of English in non-English-speaking contexts has raised concerns about heritage language maintenance and identity preservation. In Lithuania, English increasingly functions as a language of education, work, and international communication, while Lithuanian remains central to national and cultural identity. This qualitative case study investigated language-use patterns, heritage language maintenance, and identity preservation among three Lithuanian–English bilinguals in Kaunas. Data were collected through semi-structured interviews and limited observations across family, education, and community domains. The analysis was guided by Setiawan’s (2013) domain-based language-use framework and Fishman’s theory of language maintenance. The findings show that participants used Lithuanian and English differently across domains. English was dominant in educational, professional, and international interactions, while Lithuanian remained important in family communication, local interactions, cultural practices, and media engagement. Participants maintained Lithuanian through intergenerational communication, positive language attitudes, cultural participation, and exposure to Lithuanian songs, books, and community practices. Although English served important practical and global functions, participants continued to associate Lithuanian with belonging, heritage, and cultural continuity. The study suggests that heritage language maintenance depends not only on frequency of use but also on emotional attachment, family transmission, and cultural identification.